Pengaruh Dana Perimbangan dalam Mengurangi Ketimpangan Pendapatan di Indonesia - Dina Marsella; Rindu Rika Gamayuni (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the effect of balancing funds consisting of revenue sharing funds (DBH), general allocation funds (DAU), physical special allocation funds (DAK physical), health operational assistance funds (DBOK), and education operational assistance funds (DBOP) on income inequality as measured by the Gini ratio in 34 provinces in Indonesia during the period 2020-2024. This study uses a quantitative approach with panel data regression methods. The data used is secondary data obtained from the Central Statistics Agency and the Directorate General of Fiscal Balance, Ministry of Finance. The findings of this study indicate that the allocation of DBH and DAU has a negative and significant effect on reducing income inequality. Meanwhile, the allocation of DAK physical and DBOK has not had a significant effect on income inequality. In addition, DBOP has a positive and significant effect on income inequality. It is hoped that local governments can improve their financial management so that the function of fiscal equalization funds to equalize regional development, reduce income inequality, and improve the welfare of the community can be achieved optimally and not only felt by a few parties.